Phytochemical studies of Helichrysum armenium subsp. armenium and its antioxidant, acetylcholinesterase, and antimicrobial activities - TAŞKIN, TURGUT (My University, 2024)
Helichrysum armenium subsp. armenium plant was extracted with the Soxhlet apparatus. The obtained extract was fractionated and, respectively, AHB (petroleum ether–60% ethanol-chloroform), AHC (ethanol-toluene), AHD (ethanol-chloroform), and AHE (ethanol-ethylacetate) extracts were obtained. Then, antimicrobial, antioxidant, and acetylcholinesterase activity studies were performed on these extracts. In this study, with the using the LC-HRMS method from the aerial parts of Helichrysum armenium subsp. armenium, the flavonoids: apigenin, apigenin 7-glucoside, apigenin 7-methylate, luteolin 7-glucoside, kaempferol, quercetin, quercitrin, (+)-trans taxifolin, (-)-epicatechin gallate, sinensetin, rutin, 3\"-o-methyl quercetin, hispidulin, chrysin, acacetin, genkwanin, chrysoeriol; the phenolic acids: chlorogenic acid, ascorbic acid, fumaric acid, caffeic acid, salicylic acid, caffeic acid phenethyl ester, emodin, vanilic acid; the alkaloid: caffeine and the saponoside; glycyrrhizic acid were obtained.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); acetylcolinesterase; antimicrobial; antioxidant; Helichrysum armenium subsp. armenium; LC-HRMS; phenolic compounds